2009
DOI: 10.19030/ajbe.v2i7.4582
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Performance On The Business Environment And Concepts Section Of The CPA Exam

Abstract: This paper examines how differences in curricular design of undergraduate accounting programs influence pass rates on the Business Environment and Concepts Section of the CPA Exam. The association of the pass rate of a school's accounting graduates to the design of the schools accounting program and to other school characteristics was examined with linear regression models. Characteristics considered were semester hours in courses covered by the CPA exam section, entrance exam scores of the schools' freshmen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…They found that students who graduated from an AACSB-accredited institution were significantly more likely to pass in one or two attempts. Lindsay, Tan, and Campbell (2009) studied candidate performance on just the Business Environment section of the exam and their findings related to AACSB schools also reinforced the Howell and Heshizer study. Lindquist and Smith (2013), Lopez and Specht (2009), Paul (2004), Lasch (2005), and Akers, Giacomino, Courtney, and Johnson (2014) examined the top schools' success on the computerized exam as compared to the paper-and-pencil exam and found that there were some changes in the top schools with the new exam format.…”
Section: Introductionmentioning
confidence: 60%
“…They found that students who graduated from an AACSB-accredited institution were significantly more likely to pass in one or two attempts. Lindsay, Tan, and Campbell (2009) studied candidate performance on just the Business Environment section of the exam and their findings related to AACSB schools also reinforced the Howell and Heshizer study. Lindquist and Smith (2013), Lopez and Specht (2009), Paul (2004), Lasch (2005), and Akers, Giacomino, Courtney, and Johnson (2014) examined the top schools' success on the computerized exam as compared to the paper-and-pencil exam and found that there were some changes in the top schools with the new exam format.…”
Section: Introductionmentioning
confidence: 60%
“…Research suggests that, in general, nonminority students have higher pass rates for the CPA Exam than minority students (Booker, 2005;Espahbodi et al, 2023;Appendix). Studies show that candidates graduating from institutions that have accreditation, such as the Association to Advance Collegiate Schools of Business (AACSB) or the AACSB-A, the Accreditation Council for Business Schools and Programs (ACBSP), have higher CPA Exam pass rates than candidates that graduated from institutions without those accreditations (Read et al, 2001;Barilla et al, 2008;Lindsay et al, 2009). Boone et al (2006) found that the correlation between AACSB accreditation and pass rate is due to "student selectivity" criteria.…”
Section: The Pipelinementioning
confidence: 99%
“…Numerous researches have been performed to find out the factors leading to CPA examination success in various countries (see for example, USA: Dunn & Hall, 1984;Titard & Russell, 1989;Shbaugh & Thompson, 1993;Campbell, Lindsay, & Foote, 2000;Brahmasrene & Whitten, 2001;Whitten & Brahmassrene, 2002;Howell & Belk, 2003. Cocozza, 2005Howell & Heshizer, 2006;Boone, Legoria, Seifert, & Stammerjohn, 2006;Charron & Lowe, 2009;Lindsay et al, 2009;Metinko & Gray, 2010;Lindquist & Smith, 2013;Lightweis, 2014;Hahn & Fairchild, 2015;Morgan, 2015;Hahn & Fairchild, 2015;Trinkle et al, 2016;Nigeria: Odia & Ogiedu, 2013. Jordan: Momany, 2013Abd-Al-Jaleel & Thaher, 2015.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…They found that candidates prefer to take a computerized exam. Lindsay et al (2009) examined the relationship between the design of undergraduate accounting programs and the passing rates of the CPA exam. They found that the cost and managerial accounting semester hours play important factors of passing the new part of the CPA exam.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%